Caspase isoforms in inflammasome activation - Digby, Zsofia (University of Cambridge, 2020)
Inflammasomes are macromolecular signalling platforms composed of a receptor (for example NLRP3 or NLRC4), an adaptor (ASC) and effectors (caspases) that are thought to play critical roles in the host defence against microbial infections. Activation of inflammasomes leads to the processing of the pro-inflammatory cytokines pro-IL-1β and pro- IL-18 to their active form and cleavage of gasdermin D to induce pyroptosis. Caspase-1 is the main inflammatory caspase responsible for cytokine maturation and induction of cell death, while human caspase-4, -5 and the mouse orthologue caspase-11 play an essential role in cytosolic bacterial LPS recognition. The putative importance of inflammasomes suggest that their constituents should be conserved across different animal species, but there are major differences, particularly in the caspase repertoire, in both invertebrates and vertebrates. The dog (Canis lupus familiaris), for example, has a pseudogene for NLRC4 and has a unique caspase-1/4/11 hybrid gene (CASP1-4/5/11) comprising the caspase-1 caspase recruitment domain (CARD) and the catalytic domain of caspase-4/5/11. Dogs produce bioactive IL-1β despite the apparent lack of the catalytically active domain of caspase-1, but how this occurs and whether inflammasome activation of CASP1-4/5/11 is required remains to be resolved. In this study I characterised inflammasome function in dog macrophages (DH82 cell line) and mouse macrophages where a caspase 1/4/11 fusion protein that is functional equivalent to CASP1-4/5/11 (DogMo) had been generated by CRISPR/Cas9 gene editing. I used imaging (ASC and active caspase speck formation), cell death analysis and IL-β production as readouts before and after editing of key genes in inflammasome formation using CRISPR-Cas9 gene editing approaches. The NLRP3 inflammasome is functional in dog macrophages, but the rate of inflammasome formation is lower compared to wild-type murine macrophages. This suggests that dog macrophages may be adapted to be tolerant to NLRP3 inflammasome ...